0370 Polysomnography following an indeterminate HSAT: Low Compliance with AASM Guidelines. (25th May 2022) - Nygate, Yoav; Rusk, Sam; Turkington, Fred; Fernandez, Chris; Glattard, Nick; Sprague, Matt; Winzurk, Zac; Watson, Nathaniel
Abstract: Introduction: Home sleep apnea test (HSAT) provides a low risk, cost-effective, and convenient diagnostic test for obstructive sleep apnea (OSA) in adult patients. However, in situations where HSAT are inconclusive, technically inadequate, or produce a negative result, the American Academy of Sleep Medicine (AASM) strongly recommends that a polysomnography (PSG) be performed. In this study, we evaluate whether patients are likely to comply with receiving a follow-up PSG following an indeterminate HSAT to rule out any presence of OSA and assess the demographic characteristics of individuals who are more likely to follow the AASM guidelines. Methods: In order to assess routine compliance with the AASM follow-up guidelines, we have conducted an observational study with N=3, 049 patients that received a HSAT in 2019 from 6 independent AASM accredited sleep centers across the U.S. The patient sample included 39.8% female and 60.2% male. 30.34% from the 19-44 age group, 47.2% from the 45-64 age group, and 21.2% from the 65-84 age group. Furthermore, 33% of the patients received a negative HSAT and were advised for a follow-up PSG. Results: 14.8% of patients who received a negative HSAT in 2019 underwent a follow-up PSG by the end of 2021. Male patients and patients who are younger in age were more likely to follow the AASM guidelines. 16.4% of male patients and 9% of female patients who received a negative HSAT underwent a follow-up PSG. 17.7% of patients aged 19-44 who received a negative HSAT received a follow-up PSG, while only 11.1% of patients aged 45-64, and 7.6% of patients aged 65-84 conformed with the AASM guidelines and followed-up with a PSG. Conclusion: The overall percentage of patients who comply with the AASM guidelines is relatively low at 14.8%. Emphasis should be put on patient outreach and education to improve this statistic. Such endeavors may try to target female and older patients who appear to be slightly less compliant with AASM guidelines. Simultaneously, more attempts should be made to improve HSAT to increase OSA specificity and decrease the necessity for a follow-up PSG, as this AASM guideline is often overlooked by patients. Support (If Any):